Analysis of Increasing Regional Economic Competitiveness in the Agricultural Sector in Increasing Regional Economic Growth - Ilham Ilham; Hardianti Yusuf; hamdani thaha; Nurul Hamida (IAIN Palopo, 2021)
The rate of economic growth continues to decline As a result of the declining rate of growth of gross domestic product, the number of poor people increases. Various steps have been taken by the government to increase economic growth by utilizing local resources in each region.This study aims to explain the role of the agricultural sector in efforts to increase regional economic growth in East Luwu Regency and the competitiveness of the agricultural sector. This research uses quantitative methods with data analysis using Location Quotient (LQ), Shift Share (SS), Klassen Typology and Market Structure Analysis . The results of this study show that the LQ analysis and Klassen typology analysis show that the agricultural sector is a potential sector and can still grow. The implication of the article is that local governments must encourage agricultural productivity, transform towards agro-industry and increase market share as well as provide agricultural product processing facilities to increase product selling value